Synthesis and Characterization of Cobalt(II) Complexes with Hemilabile P^N Donor Ligands - Gogoi, Rajjyoti; Pathak, Chandan; Borah, Geetika (Asian Journal of Chemistry, 2019)
Two cobalt(II) complexes viz. CoCl2PPh2(p-C6H4NMe2)2 (C1) and CoCl2(PPh2Py)2 (C2) were synthesized by reacting CoCl2·6H2O and 4-(dimethylamino)phenyldiphenylphosphine and diphenyl-2-pyridylphosphine ligands, respectively. The complexes were characterized by elemental analysis, FT-IR, UV-visible and electronic spin resonance (ESR) spectroscopic technique. Both the complexes were found stable at room temperature. EPR measurements and UV-visible spectra analysis of C1 and C2 are consistent with a tetrahedral Co(II) and tetragonally distorted octahedral Co(II) ions, respectively.